2021
DOI: 10.2337/cd20-0034
|View full text |Cite
|
Sign up to set email alerts
|

Practical Strategies to Help Reduce Added Sugars Consumption to Support Glycemic and Weight Management Goals

Abstract: Overconsumption of added sugars is a key contributor to the growing obesity, prediabetes, and type 2 diabetes pandemics. The nutrition therapy guidance of the American Diabetes Association recognizes that using low- and no-calorie sweeteners (LNCS) to reduce consumption of added sugars can reduce low–nutrient-density sources of calories and carbohydrate to beneficially affect glycemia, weight, and cardiometabolic health. This article provides information for primary care providers, diabetes care and education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…The growing pandemic of obesity and T2D has led to the implementation of efforts to promote healthier eating habits and to contrast the overconsumption of added sugars [90,91]. In this context, low-calorie sweeteners (LCSs) have gained a role in maintaining a sweet taste without adding extra energy, as occurs with foods and drinks containing added (or caloric) sugars [90].…”
Section: Low-calorie Sweetenersmentioning
confidence: 99%
See 3 more Smart Citations
“…The growing pandemic of obesity and T2D has led to the implementation of efforts to promote healthier eating habits and to contrast the overconsumption of added sugars [90,91]. In this context, low-calorie sweeteners (LCSs) have gained a role in maintaining a sweet taste without adding extra energy, as occurs with foods and drinks containing added (or caloric) sugars [90].…”
Section: Low-calorie Sweetenersmentioning
confidence: 99%
“…Recently, some authors have suggested that LCSs reduce energy intake and may promote weight loss when substituted for caloric sugars (such as sucrose) [91,93]. As a consequence, LCSs could be a strategy to consider to lower the prevalence of obesity and T2D [91,94].…”
Section: Low-calorie Sweetenersmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all low/no calorie sweeteners are as stable as sucralose in foods, 22 meaning sucralose can be used to replace sugar in some applications where other sweeteners cannot. In general, low-calorie sweeteners approved for use have been recognized as a way to help reduce carbohydrate intake, important, for example, in diabetes meal planning 23,24 and to help reduce caloric intake, which can aid in weight management strategies. [25][26][27] In addition, sucralose is used already in many food applications.…”
Section: Introductionmentioning
confidence: 99%